Programmable multi-bladder pneumatic tourniquet cuff - Tajaddod, Amir Mohammad Ebrahimi (2012)
Pneumatic Tourniquet cuff device is used in limb orthopedic surgery especially in the upper limb to provide a bloodless field it can be obscured by blood.The tourniquet cuff occludes both venous and arterial supply. In the process there is also compression of the nerve and this can result in pneumatic tourniquet cuff system paralysis. When the operation is done under regional or local anesthesia the patient may experience discomfort at the site of application. This shortens the duration of the pain tolerence and hence lengthy operation can not be carried out under local or regional anesthesia. Since many operations may be carried out under local or regional anesthesia, a pneumatic tourniquet cuff system had been defigned which may help to increase the pain tolerence. The multicompartment pneumatic tourniquet cuff system with multiple bladders each with its own pumps to inflate and deflate each tourniquet cuff is implemented to produce a bloodless field. A microcontroller controls each tourniquet cuff to be inflated and deflated. The pressure effect on the underlying structures is then reduced while maintaining a bloodless field. This tourniquet cuff system comprises of pump unit, microcontroller and a cuff with three compartments. The pump unit is AC powered operates to inflate at a preset pressure. There is a valve and a pressure transducer which is responsible to maintain the pressure at a preset level. Depending on the signal recieved from the microcontroller the sequence of open and close the three valves are regulated. The tourniquet had 3 compartments non structuring fabric is used to form the three compartments into 3 bladders are inserted. The bladder is a sealed bladder with only inlet or outlet which is provided by the tubing. The operation of the system is controlled by a microcontroller. This unit is turned on and the pressure required is set. The inflate button is turned on. Based on the programming done the inflation of the proximal torniquet followed by the middle and distal tourniquet is done followed by the reverse sequence,thus maintaining the occlusion to provide a bloodless field but relieving pressure at the site of the tourniquet. Hence reducing the discomfort and relieving the pressure on the underlying structures especially the nerve.